SOCIO-POLITICAL FACTORS OF TERRORIST GROUPS EXISTENCE IN ISLAMIC STATES - Целуйко, М. Є. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2021)
The question about socio-political conditions in Islamic states, which may affect the activities of terrorist organizations is considered. The countries of the Middle East are most often faced with terrorist activity. The population of these countries may be ethnically diverse or homogeneous, but the overwhelming majority professes Islam - a religion that has spiritual, legal and socio-political principles, offers an alternative approach to the foundations of the state system and the principles of its functioning. Islamism as a political trend has its supporters among both moderate and radical social groups in these countries. The ruling elites of some countries proclaims Islam the state religion with the appropriate preferences for it. However, Islamic states no less, and sometimes more than other countries in these regions, suffer from the activities of terrorist groups.A number of socio-political characteristics that take place in Islamic states is highlighted, and their possible connection with the emergence and further activities of terrorist groups in any direction (from collecting information and recruiting local people to preparing and conducting a terrorist attack) is considered. Attention is paid to the relationship between the stability of the political system in Islamic states and their controllability of the territory within their own borders with the presence and type of the activities of terrorist organizations. The mutual importance of the problems of security, education, living conditions and features of the political regime in the issue of the risk of the emergence and further existence of terrorist groups in the Islamic state is accented.The necessity of a complex of factors for the existence of a terrorist group is emphasized. It is noted that this complex is different for the constant or short-term activities of terrorists. The deterioration of the situation regarding the existence and activities of terrorists in the country is the greater, the more threatening factors appear, the less important will be the features of the political regime. The priority of individual factors in the presence of various situations is established type.